Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share - Ilham Rahmat Kurniawan; Ani Fiani; Eka Lokaria (Journal of Elementary School (JOES), 2023)
his study aims to determine the application of the Cooperative Learning Model of the Think Pair Share Type in Mathematics Learning for Class V MI PN Rupit. This research method is pre-experimental, with the design used is one-group pretest-posttest design. The population in this study were all students of class V MI PN Rupit, namely 30 students in VA class and 28 students in VB class. Sampling was taken by means of purposive sampling technique, namely in the VB MI PN Rupit class, there were 28 students as the sample class. Data collection techniques using multiple choice tests. Data analysis technique with steps: normality test and t test. Based on the results of the t-test analysis with the level of confidence obtained α = 0.05 data tcount = 7.18 and ttable = 1.703, the data shows that the tcount value > ttable. The students' pretest average score was 56.19 and the posttest average score was 80.24, so it can be said that H0 was rejected and Ha was accepted. Thus it can be concluded that the application of the Think Pair Share cooperative learning model in mathematics learning for fifth grade students of MI PN Rupit is significantly complete. Keywords: Learning Outcomes, Think Pair Share.